A practical and safe alternative method for skeletal cleaning for museum specimens using superworms (Zophobas morio) - Fatemeh Rastekar; Niloofar Alaei Kakhki; Mansour Aliabadian; Morteza Monfared (PLoS ONE, 2026)
Clean and undamaged skeletons that maintain natural anatomical shape are essential for anatomical collections and natural history museums. Conventional methods, such as maceration, chemical treatments, or dermestid beetle colonies, although commonly used, often require long processing times, pose biohazard risks, and may damage delicate bones. This study explores the use of superworms ( Zophobas morio ) as a biological alternative for skeletal cleaning. Controlled cleaning trials were conducted using specimens from various vertebrate groups and a range of size classes, categorized as small, medium, and large after removal of superficial tissues. As the larva to specimen ratio strongly influences cleaning time and effectiveness, we first standardized our setup by processing all specimens in identical containers, each with approximately 700 grams of superworms, allowing us to assess the optimal ratio. Our results showed that a high larva to specimen ratio led to damage of fragile bones, while lower ratios resulted in increased cleaning times. Through multiple trials, we suggest that a larva to specimen ratio of 10–15 balances efficient cleaning with minimal risk of bone damage. Applying this ratio to additional bird skulls resulted in thorough cleaning with no observed bone damage. Superworms removed soft tissues within hours to days, depending on specimen size, and were able to clean internal cavities that are typically difficult to reach. Unlike dermestid beetle colonies, which include multiple life stages and pose a higher risk of infestation or egg dispersal, superworms are limited to the larval stage, reducing such risks. Our findings demonstrate that superworms offer a rapid, adaptable, and museum-safe alternative to conventional skeletal cleaning methods, providing an efficient and practical option for scientific and curatorial settings. Superworms are readily available from commercial breeders, and maintaining a colony is straightforward, further supporting their use as a viable alternative for skeletal preparation.